Development of exoelectrogenic bioanode and study on feasibility of hydrogen production using abiotic VITO-CoRE™ and VITO-CASE™ electrodes in a single chamber microbial electrolysis cell (MEC) at low current densities. (November 2015) - Pasupuleti, Suresh Babu; Srikanth, Sandipam; Venkata Mohan, S.; Pant, Deepak
Graphical abstract: Highlights: Single chamber membrane-free microbial electrolysis cell (MEC) was operated. High current producing bioanode was developed using farm manure on carbon felt. H2 production was studied on abiotic cathodes using energy from enriched bioanodes. VITO-CoRE™ is efficient than VITO-CASE™ in terms of hydrogen and energy recovery. Abstract: Single chamber membrane-free microbial electrolysis cell (MEC) was operated for the assessment of exoelectrogenic bacteria (EB) growth at carbon felt anode and resultant hydrogen (H2 ) production at abiotic cathodes, made using cold rolling (VITO-CoRE™) and casting (VITO-CASE™) methods. Progressive enrichment of EB was observed on anode during 70 days of operation at an applied potential of +0.2 V vs Ag/AgCl, and a maximum current density (CD) of 330.59 mA/m 2 (1.38 mA) was recorded. H2 production at selected abiotic cathodes was observed, when the enriched bioanode was coupled to them in galvanostat mode between 0.1 and 1.0 mA current range for 10 min each. Higher H2 production of 114.46 ± 3.75 mL/m 2 was documented with VITO-CoRE™ at 0.6 mA, while 102.76 ± 3.75 mL/m 2 was recorded with VITO-CASE™ at 0.8 mA of current application. This study demonstrates the feasibility of H2 production on abiotic cathodes using enriched bioanode at low current densities.